High‐fat diet induced obesity and age influence the telomere shelterin complex and telomerase gene expression in mouse adipose tissue. Issue 11 (8th June 2020) - Bloom, Samuel I.; Tuluca, Andrei; Ives, Stephen J.; Reynolds, Thomas H.
Abstract: Obesity and aging are linked to inflammation and increased risk of chronic disease. Telomeres are the endcaps of chromosomes that are regulated by telomerase, the enzyme that elongates telomeres, as well as a protein complex known as shelterin. Telomere dysfunction is associated with inflammation, aging, and disease. However, the effect of high‐fat diet (HFD) induced obesity and advancing age on the shelterin complex and telomerase in adipose tissue is unknown. The present study investigated the effects of obesity and aging on C57BL/6J mice adipose tissue mRNA expression of shelterin complex genes. Young (YG) mice (3 mo) were randomly assigned to be fed either a high‐fat diet (YG + HFD; 60% kcal from fat) or a low‐fat diet (YG + LFD; 10% kcal from fat). A subset of mice were aged until 16 months. Body weight and epididymal white adipose tissue (EWAT) weight increased with age or a HFD. There was a trend for increased Terf2 expression, as expression was increased in HFD + YG by 47% and aged mice by 80%. Pot1b expression was increased in aged mice by 35%–60% compared to YG, independent of diet. mTert, the gene that codes for the catalytic subunit of telomerase, was significantly elevated in aged mice. Changes in telomere associated gene expression was accompanied by changes in expression of inflammatory markers Mcp1 and Tnfα . These findings suggest obesity and age impact expression of shelterin complex and telomerase related genes in adipose, perhaps altering telomere function in adipose tissue thereby increasing inflammation and risk of chronic disease. Abstract : We investigated whether high‐fat diet (HFD) induced obesity or advancing age affect gene expression of the telomere shelterin complex and telomerase associated genes, as well as markers of cellular senescence and inflammation. Our findings suggest that obesity and age impact the expression of shelterin complex and telomerase related genes in adipose tissue, perhaps altering telomere function and, thereby, increasing inflammation and risk of chronic disease.